2022
DOI: 10.3389/fmolb.2021.794326
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Immune-Related Genes for Affecting Prognosis and Immune Response in Renal Clear Cell Carcinoma

Abstract: Background: In renal clear cell carcinoma, a common cancer of the urinary system, 25–30% patients are metastatic at initial diagnosis and 20–30% patients have a tendency of recurrence and metastasis after local surgery. With the rapid development of tumor immunology, immune agents have brought new directions to tumor therapy. However, no relevant studies have explored the role of immune-related genes in kidney cancer metastasis.Methods: Co-expressed metastatic immune-related differentially expressed genes (mIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…High SSTR1 expression can silence and inhibit the proliferative rate of CRC stem cells by reducing the proliferation of acetaldehyde dehydrogenase-positive cells (Modarai et al, 2016). One preliminary study (Sun et al, 2021) confirmed that SSTR1 is a target gene affecting renal cell carcinoma (RCC) metastasis and the associated immune response and could be a prognostic biological marker of and viable therapeutic target for RCC. Another study (Zhou et al, 2009) found that the antiproliferative effects of SSTR2 were both cytostatic (growth suppression) and cytotoxic (apoptosis) by affecting the cellular apoptotic level, MAPK, and angiogenic signaling molecules in SSTR2-positive and -negative cancers.…”
Section: Discussionmentioning
confidence: 99%
“…High SSTR1 expression can silence and inhibit the proliferative rate of CRC stem cells by reducing the proliferation of acetaldehyde dehydrogenase-positive cells (Modarai et al, 2016). One preliminary study (Sun et al, 2021) confirmed that SSTR1 is a target gene affecting renal cell carcinoma (RCC) metastasis and the associated immune response and could be a prognostic biological marker of and viable therapeutic target for RCC. Another study (Zhou et al, 2009) found that the antiproliferative effects of SSTR2 were both cytostatic (growth suppression) and cytotoxic (apoptosis) by affecting the cellular apoptotic level, MAPK, and angiogenic signaling molecules in SSTR2-positive and -negative cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The studies involving human participants were reviewed and approved by Ethics Committee and Institutional Review Board for Clinical Research of Zhongda Hospital (ZDKYSB077) ( 43 , 44 , 45 , 46 ). This study is a retrospective study that only collected clinical data from patients, and the ethical committee approved the exemption of informed consent.…”
Section: Ethics Statementmentioning
confidence: 99%
“…Against this backdrop, immunotherapy has recently become an effective and safe method of treating tumors ( 9 , 10 ). Immunotherapy reduces tumor metastasis and recurrence by stimulating specific immune responses to suppress and kill tumor cells ( 11 ). Research has demonstrated favorable therapeutic effects of monoclonal antibodies targeting programmed cell death protein 1 (PD-1) or programmed death-ligand 1 (PD-L1) in treating ESCC ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%